The Anatomy of Subjective Well-being - Bernard M. S. van Praag; P. Frijters; Ada Ferrer-i-Carbonell (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
Subjective Well-Being has increasingly been studied by several economists. This paper fits in that literature but takes into account that there are different aspects of life such as health, financial situation, and job. We call them domains. In this paper, we consider Subjective Well-Being as a composite of various domain satisfactions (DS). We postulate a two -layer model where individual Subjective Well-Being is explained by individual subjective domain satisfactions with respect to job, finance, health, leisure, housing, and environment. We distinguish between long -term and short - term effects. Next, we explain domain satisfactions and Subjective Well-Being by objectively measurable variables such as income. We estimate a model for the GS and DS equations with individual random effects and fix time effects.
Keywords: I31; C25; C23; 330; Subjective Well-Being; satisfaction measurement; qualitative regressors; health satisfaction; job satisfaction; Lebensqualität; Verhaltensökonomik; Arbeitszufriedenheit; Einkommen; Theorie; Deutschland; Lebenszufriedenheit